Odpowiedzi

2010-02-01T15:45:51+01:00
1. 4x+y=13
3x-2y= -4

y=-4x+13
3x-2(-4x+13)=-4

y=-4x+13
3x+8x-26=-4

y=-4x+13
11x=22

y=-4x+13
x=2

y=-4*2+13
x=2

y=-8+13
x=2

y=5
x=2

2.2x-y=1
x+2y=8

2x-y=1
x=-2y+8

2(-2y+8)-y=1
x=-2y+8

-4+16-y=1
x=-2y+8

12-y=1
x=-2y+8

-y=-11
x=-2y+8

y=11
x=-2*11+8

y=11
x=-22+8

y=11
x=-14


Najlepsza Odpowiedź!
2010-02-01T15:46:22+01:00
1. 4x+y=13
3x-2y= -4

y=13-4x
3x-2(13-4x)=-4

y=13-4x
3x-26+8x=-4

y=13-4x
11x=-4+26

y=13-4x
11x=22 /:11

y=13-4x
x=2

y=13-4*2
x=2

y=5
x=2


2. 2x-y=1
x+2y=8


2x-y=1
x=8-2y

2(8-2y)-y=1
x=8-2y

16-4y-y=1
x=8-2y

-5y=1-16
x=8-2y

-5y=-15 /:-5
x=8-2y

y=3
x=8-2*3

y=3
x=2
2010-02-01T15:49:50+01:00
1). Tylko przepisz tan przykład co podałas/es a dopiero to:
y=13-4x
3x-2(13-4x)=-4

y=13-4x
3x-26-8x=-4

y=13-4x
-5x=-4-26

y=13-4x
-5x=-30 /:(-5)
x=6
Podstawiam teraz 6 za x
4*6+y=13
24+y=13
y=13-24
y=-11



2).Tylko przepisz tan przykład co podałas/es a dopiero to:
2x-y=1
x+2y=8

-y=2x+1
x+2y=8

-y=2x+1/ :(-1)
x+2y=8

y=-2x-1
x+2(-2x-1)=8

x-4x-2=8
-3x=8+2
-3x=10 /:(-3)
x=(w ułamku)- 10/3
x=(w ułamku)-3 i 1/3